Speech Communication System Based on Piezoelectric Electret Mechanical Antenna - Shuopu Wang; Jing Yang; Ping Lu; Shaolong Yang; Limin Guo; Yanan Hao; Kai Huang; Jianchun Xu (Applied Sciences, 2023)
Low-frequency electromagnetic waves have strong penetration and low attenuation performance, making them widely used in long-wave communication areas such as underwater communication and earthquake prediction. Mechanical antennas are seen as a promising alternative to traditional low-frequency resonant antennas, as they offer the potential for miniaturization and low power consumption. However, existing communication systems using mechanical antennas are usually rudimentary, incompatible, and inconvenient to use. To address these problems, a novel speech communication system based on a piezoelectric electret mechanical antenna was proposed. This communication system includes a hardware system, a communication protocol for mechanical antennas, and a software system with a modular structure. This system includes hardware, a communication protocol, and a modular software system. The results of the experiments showed that this communication system provides real-time speech communication with a user-friendly design, high compatibility with different communication devices, and easy customization to meet specific requirements. This design holds great potential for applications in mineral detection, seismic research, submarine communication, industrial RF control, and other related mechanical antenna applications.